Infant intakes of human milk branched chain amino acids are negatively associated with infant growth and influenced by maternal body mass index. Issue 5 (16th December 2021) - Saben, Jessica L.; Sims, Clark R.; Pack, Lindsay; Lan, Renny; Børsheim, Elisabet; Andres, Aline
Summary: Background: Branched‐chain amino acids (BCAAs: isoleucine, leucine, and valine) and aromatic amino acids (AAAs: phenylalanine and tyrosine) are hypothesized to influence early‐life obesity risk. Objective: To assess HM free amino acid (AA) concentrations and infant intakes of HM AAs from women with obesity (OB) compared to those with normal weight (NW) and determine the relationships between HM AA consumption and infant growth. Methods: HM samples were collected at 0.5 ( n = 151), 2 ( n = 129), and 6 ( n = 93) months postpartum from mothers with NW (body mass index [BMI] = 18.5–24.9 kg/m 2 ) and OB (BMI > 30 kg/m 2 ). HM AAs were quantified via mass spectrometry. Infant HM intake, anthropometrics and body composition were assessed. Linear mixed‐effects models (LMEM) examined the relationships between maternal BMI and HM AA intakes, and HM AA intake and infant growth over the first 6 months postpartum after adjusting for maternal and infant characteristics. Results: Maternal BMI was positively associated with infant intakes of isoleucine, leucine, and AAAs across timepoints. HM AA intakes were positively associated with weight‐for‐length z ‐score, fat mass index, and fat‐free mass index in infants ( p < 0.05). Conclusions: Maternal BMI led to differences in HM AA composition, which was associated with infant body composition.